2016
DOI: 10.1525/collabra.39
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Sensitivity to Style During Literary Reading: Insights from Eye-Tracking

Abstract: Style is an important aspect of literature, and stylistic deviations are sometimes labeled foregrounded, since their manner of expression deviates from the stylistic default. Russian Formalists have claimed that foregrounding increases processing demands and therefore causes slower reading -an effect called retardation. We tested this claim experimentally by having participants read short literary stories while measuring their eye movements. Our results confirm that readers indeed read slower and make more reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 50 publications
3
29
0
Order By: Relevance
“…Pynte, New, and Kennedy (2008) found that larger LSA distance between the current and previous content word(s) results in longer word-reading time but this effect could have been caused by a confound with predictability (Frank, 2017). Indeed, Van den Hoven, Burke, and Willems (2016) did not find a reading time effect of semantic distance over and above surprisal.…”
Section: Models Of Syntagmatic and Paradigmatic Relationsmentioning
confidence: 78%
See 1 more Smart Citation
“…Pynte, New, and Kennedy (2008) found that larger LSA distance between the current and previous content word(s) results in longer word-reading time but this effect could have been caused by a confound with predictability (Frank, 2017). Indeed, Van den Hoven, Burke, and Willems (2016) did not find a reading time effect of semantic distance over and above surprisal.…”
Section: Models Of Syntagmatic and Paradigmatic Relationsmentioning
confidence: 78%
“…It is quite remarkable that the two measures have the same effect size, in the sense that one standard deviation increase in either measure resulted in the same amount of increase in N400 size, considering that predictability effects are much more robust than semantic relatedness effects, at least in reading times (Camblin et al, 2007;Frank, 2017;Van den Hoven et al, 2016). Camblin et al (2007) found that N400 effects of discourse congruency (which correlates with predictability) precede those of priming.…”
Section: Discussionmentioning
confidence: 99%
“…Especially if we use literary texts such as poems not specially designed for research (Bailey and Zacks, 2011;Willems and Jacobs, 2016), simple or complex text features seldom occur without interacting with many other features on various levels. Although there have been studies on the reading of literary texts or poems (e.g., Sun et al, 1985;Lauwereyns and d'Ydewalle, 1996;Carrol and Conklin, 2014;Dixon and Bortolussi, 2015;Jacobs et al, 2016a,b;van den Hoven et al, 2016;Müller et al, 2017), the vast majority of eye tracking studies on reading were constrained to experimental textoids and tested only a few selected features while ignoring many others (Rayner et al, 2001;Reichle et al, 2003;Engbert et al, 2005;Rayner and Pollatsek, 2006;Rayner, 2009).…”
Section: Eye Movement Research On Poetry Readingmentioning
confidence: 99%
“…For example, in our two sonnets, ART got the sonscore of 10 × 1 [a] + 7 × 1 [r] + 1 × 1 [t] = 18/SQRT (3) = 10.39. As shown in Table 2, some of these psycholinguistic features were highly correlated, hence the need to apply machine-learning tools in a predictive approach (e.g., Coit et al, 1998;Francis, 2001;Tagliamonte and Baayen, 2012;Yarkoni and Westfall, 2017).…”
Section: Psycholinguistic Featuresmentioning
confidence: 99%
“…Making meaning of a literary text or poem requires more than comprehending words and sentences, in particular the mental (re-)construction of the situations described by a text-situation models-hypothesized to arise through the integration of a reader's knowledge of the world with information explicitly presented in a text (Bower & Morrow, 1990;Kintsch & van Dijk, 1978;van den Broek, 2010;Zwaan, 2016). Important cognitive subprocesses are inferences for bridging successive events/situations, the use of background knowledge and discourse context, and pragmatic interpretations.…”
Section: Inference and Situation Model Buildingmentioning
confidence: 99%